Identification of electrofacies on the basis of well logging to determine sedimentation environment of horizon JK[2] in Em-Egovskoe field (Western Siberia); IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Kudryashova L. K. Lidiya Konstantinovna (Petroleum Geology. Current Exploration and Extraction Methods, 2015)
Title screen